PERANCANGAN “QAHWATCH” SEBAGAI INOVASI JAM TANGAN AROMATERAPI DENGAN MEMANFAATKAN AMPAS KOPI DAN SERBUK KAYU SEBAGAI PENGOLAHAN LIMBAH - Maulana, Arief Farhan (Jurnal Teknologi Lingkungan Lahan Basah, 2020)
Abstract Indonesia is an agricultural country that is fertile enough to use as plantation land. West Kalimantan is recorded as the highest amount of 4,030 tons of coffee production in 2015. The city government also has plans to realize Pontianak as a city of 1000 Coffee Shop by building the Gajah Mada Coffee Street area as a coffee center of Pontianak. The rapid development of the coffee industry poses problems for the environment. Qahwatch method is present as an alternative by a combination of the basic ingredient of coffee grounds processed into watches along with sawdust and resin as a mixture. This method can create watches that are environmentally friendly with a touch of new technology. The research method used secondary data obtained from searching for various libraries in the form of articles, journals, and the internet. The process of making Qahwatch is divided into 4 stages, namely Mixing, Molding, Assembling, and Finishing. The development of Qahwatch can improve product excellence in terms of purpose, durability, comfort, coffee content, brand, quality, design, multifunctional, trendy model, non-allergenic, and waterproof. The birth of the Qahwatch method is not only a reduction in the amount of waste in Indonesia, but it can also increase the economic added value of coffee grounds waste . These results indicate that the opportunity of the plantation industry in processing coffee grounds waste is very feasible to be developed.Keywords: Qahwatch; coffee grounds waste; sawdust, aromatheraphy, environment Abstrak Indonesia merupakan negara Agraris yang cukup subur untuk dijadikan lahan perkebunan. Kalimantan Barat tercatat menduduki jumlah tertinggi produksi kopi di perkebunan yaitu 4.030 ton ditahun 2015. Pemerintah Kota pun memiliki rencana untuk mewujudkan kota Pontianak sebagai Kota 1000 Warung Kopi dengan membangun kawasan Gajah Mada Coffee Street sebagai pusat kopi di Pontianak. Pesatnya perkembangan industri kopi menimbulkan masalah bagi lingkungan. Metode Qahwatch hadir sebagai alternatif dengan menggunakan metode kombinasi dari bahan dasar ampas kopi yang diolah menjadi jam tangan beserta serbuk kayu dan resin sebagai pencampurannya. Metode ini dapat menciptakan jam tangan yang ramah lingkungan dan aromaterapi dengan sentuhan teknologi baru. Metode penelitian digunakan data sekunder yang diperoleh dari penelusuran berbagai pustaka berupa artikel, jurnal, dan internet. Proses pembuatan Qahwatch dibagi menjadi 4 tahapan, yakni Mixing, Moulding, Assembling, dan Finishing. Perkembangan Qahwatch dapat meningkatkan keunggulan produk dalam segi tujuan, ketahanan, kenyamanan, kandungan kopi, merek, kualitas, desain, multifungsi, model trendi, tidak menimbulkan alergi, dan tahan air. Lahirnya metode Qahwatch tidak hanya mengurangi jumlah sampah di Indonesia, tetapi juga dapat meningkatkan nilai tambah ekonomi limbah ampas kopi. Hasil tersebut membuktikan bahwa peluang industri perkebunan dalam mengolah limbah ampas kopi sangat layak untuk dikembangkan.Kata Kunci: Qahwatch; limbah ampas kopi; serbuk kayu; aromaterapi; lingkungan